The “Rebuff Chorus” in 1960–2000 Pop Music - David Heetderks (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2023)
In some verse–prechorus–chorus (VPC) songs from 1960–1990, the prechorus sets up an expectation for tonic arrival, only to have the subsequent chorus reject this tonal implication and either withhold tonic resolution, abruptly change to a new key, or contain a passage whose relation to the previous one is tonally ambiguous. I call this event a “rebuff” chorus. Formal analysis and intertextual comparison show how rebuff choruses use absent-tonic passages or modulatory “breakout” passages in order to swerve away from the implications of the previous section. The formal device often transforms the expressive effect of the chorus from arrival and sincerity into frustration, puzzlement, or searching. The article examines the harmonic layout and text–music relations in rebuff choruses in examples from 1960s–70s Motown and R&B, the Talking Heads, and several songs by the indie-rock band R.E.M., among other artists.
Keywords: Pop/Rock; Form; Verse-Prechorus-Chorus; Prechorus; Tonality; Rock Tonality; Breakout Chorus; Motown; R.E.M.; Talking Heads; Kate Bush